Potential role of CFLAR in enhancing 5-FU sensitivity and modulating immune cell infiltration in breast cancer - Yuwei Sun; Weilun Fang; Jinwu Peng; Xingling Liu; Chunjiang Wang; Liying Song; Zhenzhen Deng (European Journal of Medical Research)
Abstract Background Breast cancer (BRCA), the most common malignancy among women, is a highly heterogeneous disease. Chemoresistance is a major factor leading to treatment failure in BRCA. However, mechanisms underlying the development of chemoresistance remain unclear. Methods In this study, we performed a comprehensive bioinformatic analysis to examine the role of cell death-associated genes in BRCA treatment. Specifically, we focused on caspase 8 and Fas-associated protein with death domain-like apoptosis regulator (CFLAR), which was identified as a co-differentially expressed cell death-associated molecule with potential prognostic values. We then validated these findings through in vitro experiments in BT- 549 and MDA-MB- 231 breast cancer cells. Results Based on bioinformatics analysis, CFLAR expression was found to be downregulated in patients with BRCA, whereas its high expression was significantly associated with improved prognosis. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated that aberrantly expressed CFLAR was potentially associated with oxidative phosphorylation, T cell receptor signaling, and NADH dehydrogenase (ubiquinone) activity. In vitro experiments demonstrated that overexpression of CFLAR inhibited the generation of reactive oxygen species (ROS), consequently promoting 5-fluorouracil (5-FU) sensitivity in BT- 549 and MDA-MB- 231 breast cancer cells. The expression of CFLAR was positively correlated with the abundance of several tumor-infiltrating immune cells, especially CD8 + T cells, further supporting the role of CFLAR in immune regulation. Conclusion In conclusion, this study reveals the novel roles of CFLAR in enhancing chemotherapy sensitivity and patient outcome in BRCA and underscores its potential as a therapeutic target. These results supported CFLAR as a therapeutic target and prognostic biomarker in BRCA patients.